The Influence of Organizational Culture and Organizational Commitment on the Performance of Employees of the Central Statistics Agency of Depok City: PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI BADAN PUSAT STATISTIK KOTA DEPOK - Kuswahyuningdyah, Sri Handayani; Permata, Sherryliana; Adriza; Sukiman (Ekonomipedia: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
Abstract. Employee performance is a crucial determinant of the success of public organizations, including the Central Bureau of Statistics (BPS) of Depok City, which plays a strategic role in providing development data for government and society. In the context of modern bureaucracy, improving performance is not only determined by technical competence but also influenced by internal organizational factors such as organizational culture and employee commitment. This study aims to examine the effect of organizational culture and organizational commitment on employee performance at BPS Depok City. A quantitative method with a survey approach was employed, involving all 33 employees through a census technique. The research instrument was a questionnaire that had been tested for validity and reliability, while the data were analyzed using multiple linear regression. The results indicate that organizational culture has a significant effect on employee performance (t = 2.217; p = 0.034), as does organizational commitment (t = 2.921; p = 0.007). Simultaneously, both variables significantly influence performance (F = 30.238; p = 0.000) with a contribution of 62.1 percent. These findings highlight the importance of strengthening organizational culture and enhancing employee commitment to support bureaucratic effectiveness and improve the quality of public services at BPS Depok City. Abstrak. Kinerja pegawai merupakan salah satu faktor utama dalam menentukan keberhasilan organisasi publik, termasuk Badan Pusat Statistik (BPS) Kota Depok yang memiliki peran strategis dalam menyediakan data pembangunan bagi pemerintah dan masyarakat. Dalam menghadapi tuntutan birokrasi modern, peningkatan kinerja tidak hanya bergantung pada aspek teknis, tetapi juga dipengaruhi oleh faktor internal organisasi seperti budaya organisasi dan komitmen pegawai. Penelitian ini bertujuan untuk menganalisis pengaruh budaya organisasi dan komitmen organisasi terhadap kinerja pegawai BPS Kota Depok. Penelitian menggunakan metode kuantitatif dengan pendekatan survei sensus terhadap seluruh pegawai berjumlah 33 orang. Instrumen penelitian berupa kuesioner yang telah diuji validitas dan reliabilitas, sedangkan analisis data dilakukan melalui regresi linier berganda. Hasil penelitian menunjukkan bahwa budaya organisasi berpengaruh signifikan terhadap kinerja pegawai (t = 2,217; p = 0,034), demikian pula komitmen organisasi (t = 2,921; p = 0,007). Secara simultan, kedua variabel berpengaruh signifikan (F = 30,238; p = 0,000) dengan kontribusi 62,1 persen. Temuan ini menegaskan pentingnya penguatan budaya organisasi dan peningkatan komitmen pegawai untuk mendorong efektivitas birokrasi serta meningkatkan kualitas pelayanan publik di BPS Kota Depok.